Sequence analysis of scrA and scrB from Streptococcus sobrinus 6715. - Chen, Y Y (1993)
The complete nucleotide sequences of Streptococcus sobrinus 6715 scrA and scrB, which encode sucrose-specific enzyme II of the phosphoenolpyruvate-dependent phosphotransferase system and sucrose-6-phosphate hydrolase, respectively, have been determined. These two genes were transcribed divergently, and the initiation codons of the two open reading frames were 192 bp apart. The transcriptional initiation sites were determined by primer extension analysis, and the putative promoter regions of these two genes overlapped partially. The gene encoding enzyme IIScr, scrA, contained 1,896 nucleotides, and the molecular mass of the predicted protein was 66,529 Da. The hydropathy plot of the predicted amino acid sequence indicated that enzyme IIScr was a relatively hydrophobic protein. The gene encoding sucrose-6-phosphate hydrolase, scrB, contained 1,437 nucleotides. The molecular mass of the predicted protein was 54,501 Da, and the encoded enzyme was hydrophilic. The predicted amino acid sequences of the two open reading frames exhibited approximately 45 and 70% identity with those encoded by scrA and scrB, respectively, from Streptococcus mutans GS5. Homology also was observed between the N-terminal region of the S. sobrinus 6715 enzyme IIScr and other enzyme IIs specific for the glucopyranoside molecule, all of which generate glucopyranoside-6-phosphate during translocation and phosphorylation of the respective substrates. The sequence of the C-terminal domain of the S. sobrinus 6715 enzyme IIScr shared significant homology with enzyme IIIGlc from Escherichia coli and Salmonella typhimurium and with the C-terminal domain of enzyme IIBgl from E. coli, indicating that the two functional domains, enzyme IIScr and enzyme IIIScr, were covalently linked as a single polypeptide in S. sobrinus 6715. The deduced amino acid sequence of the gene product of S. sobrinus scrB shared strong homology with sucrase from Bacillus subtilis, Klebsiella pneumoniae, and Vibrio alginolyticus, suggesting conservation based on the physiological roles of these proteins.